Setting the Stage: Key Debates and Developments from SB62 Week 1 - Koren, Judith; Miranda, Daniela (CGIAR System Organization, 2025)
Following Week 01 of SB62 in Bonn, CGIAR published a blog offering a high-level overview of its engagement to date and detailing the state of negotiations across seven key negotiation tracks. The post also shares updates related to COP30 discussed during SB62 and outlines what to expect in Week 2, highlighting how CGIAR will continue working to elevate agriculture and food systems within the climate agenda.